1999
DOI: 10.1063/1.369338
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric thin films grown on tensile substrates: Renormalization of the Curie–Weiss law and apparent absence of ferroelectricity

Abstract: A thermodynamic theory is used to calculate the dielectric properties of epitaxial thin films grown on cubic substrates imposing biaxial tension on the film prototypic cubic state. For such “tensile” substrates, the theory shows that, in a conventional plate–capacitor setup, the films should display only a monotonic variation or a broad maximum in the temperature dependence of the permittivity and an apparent absence of the hysteretic polarization behavior. Changes of the Curie–Weiss temperature and constant c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
82
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 146 publications
(89 citation statements)
references
References 18 publications
7
82
0
Order By: Relevance
“…Indeed, 33 (T) deviates from the Curie-Weiss law at about 350 K, 7,13,14 i.e., well above the Curie-Weiss temperature of the bulk material ͑297 K͒. This agrees with the behavior described by the thermodynamic theory, 8 which predicts the ferroelectric phase transition at about 415 K in a single crystalline BST film on Si.…”
supporting
confidence: 77%
See 2 more Smart Citations
“…Indeed, 33 (T) deviates from the Curie-Weiss law at about 350 K, 7,13,14 i.e., well above the Curie-Weiss temperature of the bulk material ͑297 K͒. This agrees with the behavior described by the thermodynamic theory, 8 which predicts the ferroelectric phase transition at about 415 K in a single crystalline BST film on Si.…”
supporting
confidence: 77%
“…In the aa phase, P s 2 now has a square root dependence on S m so that both linear and square root terms are involved in the explicit expression for 33 (S m ) given in Ref. 8. In order to evaluate deviations from the CurieWeiss-type law at room temperature, we computed 33 (S m ) for BT and PT films numerically.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…11 As a rule of thumb, if the buffer layer in a bilayer system is coherent and very thin relative to the substrate, then layers that are subsequently grown on top of the buffer layer will be strained to match the substrate, as though there were no buffer layer present. When the misfit strain between the two layers is of an opposite sign, as in the case for BaTiO 3 and SrRuO 3 layers on either GdScO 3 or DyScO 3 ͑Table I͒, then it will be energetically unfavorable to lose coherency at the substrate/ buffer-layer interface before losing it at the second interface. In other words, the critical thickness for a second layer on a coherent buffer layer is expected to be identical to the critical thickness in a single layer configuration, provided the strains in the two layers are of opposite signs.…”
mentioning
confidence: 99%
“…The interface structure, strain configuration, and strain relaxation in such bilayer systems are different from those in single layer systems. Here, we report transmission electron microscopy studies of epitaxial BaTiO 3 films grown on GdScO 3 and DyScO 3 substrates with buried SrRuO 3 layers. We found that the different strain relaxation behaviors observed in the bilayer are mainly dependent on lattice mismatch of each layer to the substrate and the thicknesses of each layer.…”
mentioning
confidence: 99%